1H-Indole-3-carbaldehyde azine - Rizal, M.R.; Ali, H.M.; Ng, S.W. (International Union of Crystallography, 2008)
The molecule of the title compound, C(18)H(14)N(4), lies on a center of inversion such that there is one half-mol-ecule in the asymmetric unit. The N-N single bond adopts a trans configuration and the indole fused-ring system is nearly coplanar with the -CH=N-N=CH- fragment [dihedral angle = 9.8 (2)°]. Adjacent mol-ecules are linked by indole-azine N-H⋯N hydrogen bonds into a layer motif.